Phosphorus movement in the topsoil layer after long-term surface broadcast amendment: field and controlled conditions studies - Schlindwein, Jairo Andre; Gianello, Clesio; Pequeno, Petrus Luis de Luna; Fiorelli-Pereira, Eliane Cosme; Bortolon, Elisandra Solange Oliveira (Scientia Plena, 2013)
Soils under no-till and long-term amended with phosphorus (P) applied by surface broadcast might increase its movement into the soil profile. This work sought to evaluate the soil P movement in the topsoil layer affected by the P fertilizer amounts applied by surface broadcast, comparing the soil P amounts extracted with two soil test methods. Field research and laboratory study were carried out: in the field research, a long-term experiment (Ultisol) was used to evaluate the corn and wheat yields affected by P application, and after 429 days was evaluate the P distribution in the topsoil layer; in the laboratory study was used soil columns, and were compared the P movement in two distinct soils (Ultisol and Oxisol) affected by P application; in this study we used Mehlich-1 and resin strips in different soil depths, and evaluated P movement into the soil 180 days after P application. The P movement in in the topsoil layer in the biggest dose of P in relation the control on field experiment was until 6 cm, determined for Mehlich-1 and until 10 cm determined for resin; on laboratory experiment the P movement determined for the methodologies was greater until 6 cm in the Ultisol and until 2 cm in the Oxisol. Broadcast application of soluble phosphorus in rates above that those recommended to crops increases the phosphorus availability in soil, with concentrations higher than the critical level on the soil surface, allowing the phosphorus movement in the topsoil layer, mainly in sandy soils.